Supporting spatial planning with high-spatial-resolution model-based ecosystem maps - Adam Eindride Naas; Trond Simensen; Lasse Torben Keetz; Ingrid Vesterdal Tjessem; Anders Bryn; Rune Halvorsen; Peter Horvath; Ida Marielle Mienna; Olav Skarpaas; Joachim Paul Töpper; Vigdis Vandvik; Liv Guri Velle; et al. (Environmental Impact Assessment Review, 2026)

‘Uncertainty audit’ for ecosystem accounting: Satellite-based ecosystem extent is biased without design-based area estimation and accuracy assessment - Zander S. Venter; Bálint Czúcz; Erik Stange; Megan S. Nowell; Trond Simensen; Bart Immerzeel; David N. Barton (Ecosystem Services, 2024)

Working with Natural Processes: Restoring a Mining Landscape in the High Arctic, Svalbard, Norway - Lars Erikstad; Dagmar Hagen; Trond Simensen (Geoheritage, 2023)
The Svea coal mines in Svalbard have been closed, and the area is under restoration. The goal of the landscape restoration was to enable dynamic ecological and geomorphological processes by removing roads, housing, industrial facilities, airports, landfills, and quarries that once dominated the area. Cultural heritage features, such as pre-1946 buildings, structures, and mining traces, have been preserved, while the rest of the landscape has been restored to a near-natural state. The focus has been restoring geodiversity in this arctic environment, where biotic processes are slow. Geomorphological processes such as glacial, slope, fluvial, coastal, and permafrost processes dominate and give the landscape its geological character. The objective of the restoration is not merely to re-create the landscape’s previous appearance but rather to ensure that natural processes can function as they did in the past, contributing to the ongoing development and evolution of all restored land surfaces. As of 2023, most of the area has already been restored. In areas with rapid geomorphological processes, the land will soon be dominated by these processes. Revegetation is one of the major ecological processes the restoration seeks to facilitate. Revegetation is a slow process in arctic environments, and it will take many decades before vegetation covers restored bare surfaces. The project forms a valuable baseline for studying and discussing geomorphology, landscape dynamics, geodiversity, biodiversity, and ecology for nature management and landscape restoration.

Towards a systematics of ecodiversity: The EcoSyst framework - Rune Halvorsen; Olav Skarpaas; Anders Bryn; Harald Bratli; Lars Erikstad; Trond Simensen; Eva Lieungh (Global Ecology and Biogeography, 2020)
Background Although a standard taxonomy of organisms has existed for nearly 300 years, no consensus has yet been reached on principles for systematization of ecological diversity (i.e., the co‐ordinated variation of abiotic and biotic components of natural diversity). In a rapidly changing world, where nature is under constant pressure, standardized terms and methods for characterization of ecological diversity are urgently needed (e.g., to enhance precision and credibility of global change assessments). Aim The aim is to present the EcoSyst framework, a set of general principles and methods for systematization of natural diversity that simultaneously addresses biotic and abiotic variation, and to discuss perspectives opened by this framework. Innovation EcoSyst provides a framework for systematizing natural variation in a consistent manner across different levels of organization. At each ecodiversity level, EcoSyst principles can be used to establish: (a) an extensive attribute system with descriptive variables that cover all relevant sources of variation; (b) a hierarchical‐type system; and (c) a set of guidelines for land‐cover mapping that is consistent across spatial scales. EcoSyst type systems can be conceptualized as multidimensional models, by which a key characteristic (the response) is related to variation in one or more key sources of variation (predictors). EcoSyst type hierarchies are developed by a gradient‐based iterative procedure, by which the “ecodiversity distance” (i.e., the extent to which the key characteristic differs between adjacent candidate types) is standardized and the ecological processes behind observed patterns are explicitly taken into account. Application We present “Nature in Norway” (NiN), an implementation of the EcoSyst framework for Norway for the ecosystem and landscape levels of ecodiversity. Examples of applications to research and management are given. Conclusion The EcoSyst framework provides a theoretical platform, principles and methods that can complement and enhance initiatives towards a global‐scale systematics of ecodiversity.